Determinants in Career Selection as Accountants - Octavia, Melyana; Andhaniwati, Erry (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Choosing to do accounting as a career is important because it will affect the future. This paper’s aim is to govern the effect of financial rewards, professional recognitions, profersional training, job market considerations and gender of deciding to pursue public and non public accounting as a career. The type of this research is quantitative method. The populations on this research are accounting students in semester eight and six actively studying in Universitas Negeri Jakarta and Universitas Pembangunan Nasional Veteran Jakarta. The sample was taken as many as 81 students from 415 students. All 415 samples were collected through the proportionate stratified random sampling method. The analytical techniques applied in this research is the Structural Equation Model (SEM) using Smart Partial Least Square (PLS) application program. The proportional stratified random sampling approach was used to collect the samples. Financial rewards and professional recognition have a substantial impact on career choices as accountants, though professional training, job market considerations, and gender had no impact on career choices as accountants.